The shades of the environment and the future generations in the constitutional reform (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
The constitutional reform of Articles 9 and 41 of the Constitution introduce expressly in the Italian Constitution the notions of “environment,” “ecosystem,” and “future generations”. The path that led most recently to the amendment of the Constitution was structured, on closer inspection, in the extensive constitutional jurisprudence that recognized the environment as a constitutional value and in the dialogue with international charters and catalogues that have moved in the direction of sustainability and green transition. Reference is also introduced to the protection of animals, which is transferred to the exclusive legislative competence of the state. Thus, the axiological paradigm that is the benchmark for assessing the reasonableness of public policies is changed.
Keywords: Constitutional reform; environmental protection; sustainable development; intergenerational responsibility; future generations